Thoracolumbar spine kinematics and injuries in frontal impacts with reclined occupants. (12th October 2020) - Richardson, Rachel; Jayathirtha, Mohan; Chastain, Kalle; Donlon, J.-P.; Forman, Jason; Gepner, Bronislaw; Östling, Martin; Mroz, Krystoffer; Shaw, Greg; Pipkorn, Bengt; Kerrigan, Jason
Abstract: Objective: Highly automated vehicles may permit alternative seating postures, which could alter occupant kinematics and challenge current restraint designs. One predicted posture is a reclined seated position. While the spine of upright occupants is subjected to flexion during frontal crashes, the orientation of reclined occupants tends to subject the spine to high compressive loads followed by high flexion loads. This study aims to investigate kinematics and mechanisms of loading in the thoracolumbar spine for a reclined seated posture through the use of postmortem human subjects (PMHS). Methods: Frontal impact sled tests (50 kph delta-v) were conducted on five adult midsize male PMHS seated with the torso reclined to 50 degrees with respect to the vertical. The PMHS were seated on a semi-rigid seat and restrained by a seat-integrated three-point belt with dual lap-belt pretensioners and a shoulder-belt pretensioner with a 3 kN load-limiter. 3-D kinematic trajectories of five chosen vertebrae, and the pelvis were measured relative to the vehicle buck. Intervertebral pressure transducers were installed at three locations in the lumbar column to detect load timing. Results: Three PMHS suffered fractures at L1. Combined compression and flexion of the thoracolumbar spine occurred in all tests, but the magnitude of peak flexion varied across the PMHS. During the PMHS' forward excursion, the pelvis rotated anteriorly in two tests and posteriorly in two tests (lap-belt submarining occurred in one). In one test, the pelvis mount interacted with the seat, but did not affect kinematics. Conclusions: Anterior rotation of the pelvis caused increased extension of the lumbar spine, which exacerbated lumbar compression in two of the PMHS; the one subject whose pelvis kinematic tracking was lost exhibited similar compression kinematics. Posterior rotation of the pelvis enabled lumbar flexion, which decreased lumbar compression, but lead to lap-belt submarining in one case. Lumbar kinematics for these reclined frontal impacts were sensitive to changes in initial posture of the spine (magnitude of lordosis or kyphosis) and pelvis (pitch angle). To our knowledge, this study is the first to analyze thoracolumbar kinematics and resulting injuries of a reclined seating posture using PMHS.